Cushing’s Disease Presented by Reversible Dilated Cardiomyopathy - Berna İmge Aydoğan; Demet Menekşe Gerede; Asena Gökçay Canpolat; Murat Faik Erdoğan (Case Reports in Cardiology)
Introduction. Dilated cardiomyopathy is rarely reported among CS patients especially without hypertension and left ventricular hypertrophy. Materials and Methods. We hereby report a Cushing’s syndrome case presenting with dilated cardiomyopathy. Results. A 48-year-old female patient was admitted to our clinic with severe proximal myopathy and dilated cardiomyopathy without ventricular hypertrophy. Cushing’s disease was diagnosed and magnetic-resonance imaging of the pituitary gland revealed a microadenoma. Under diuretic and ketoconazole treatments, she underwent a successful transnasal/transsphenoidal adenomectomy procedure. Full recovery of symptoms and echocardiographic features was achieved after six months of surgery. Conclusion. Cushing’s syndrome must be kept in mind as a reversible cause of dilated cardiomyopathy. Recovery of cardiomyopathy is achieved with successful surgery.